Progressive Leadership of School Principals in the Era of Independent Learning (Merdeka Belajar) - Rusmanto (al-Afkar, Journal For Islamic Studies, 2024)
Progressive Leadership is a leadership approach that emphasizes individual development, collaboration, innovation, and problem solving through the active participation and involvement of all members of a team or organization. This research aims to determine the impact of the progressive leadership of driving school principals on independent learning at SD Muhammadiyah 1 and SMA Muhammadiyah 1 Surakarta. The results of the research conducted can be concluded that (1) The role of the Principal of SD Muhammadiyah 1 and SMA Muhammadiyah 1 Surakarta can be categorized as a school leader who has a progressive leadership style, (2) The progressive leadership of the principal of SD Muhammadiyah 1 and SMA Muhammadiyah 1 Surakarta has an impact on the ability to improve students include: Thinking forward and taking innovative steps, focusing on progressive and dynamic programs, involving various parties (participative) in work and creativity, utilizing IT advances for school programs (digital leadership), inviting and mobilizing subordinates to play an active role, making decisions with consultation, consensus and democracy, has the characteristics of Asta Brata, has a prophetic nature, (3) Success factors for the progressive leadership of the head of SD Muhammadiyah 1 and SMA Muhammadiyah 1 Surakarta include government policy, funding, support from certain parties, and a good environment . Meanwhile, the failure factors were the heterogeneity of human resources in both SD and SMA Muhammadiyah 1 Surakarta as well as inadequate facilities and infrastructure.